Representing Rajasthani roots: Indian Gypsy identity and origins in documentary films. Issue 2 (November 2016) - Joncheere, Ayla; Vandevelde, Iris
Abstract : Over the past three decades, a series of documentary films featuring performing artists from Rajasthan have been produced. Extending the scholarly notion that the Roma historically migrated from India, these documentaries often portray present-day Rajasthani communities as descendants of Roma ancestors in India, and therefore as 'Indian Gypsies'. These 'realistic' films have greatly influenced public perceptions on Gypsy cultural representations and express identity politics of Gypsy unity, but have hardly been studied so far. To gain insight into both the portrayal of Rajasthani artists as Gypsies and the representation of the Indian background of the Roma, this article presents the results of a contextualized content analysis of the films, complemented by ethnographic research. It shows that the image of the Indian Gypsy is grounded in the discursive interplay between Roma politics, commercial music industries and self-exoticizing marketing by Rajasthani artists.